Oxidation of Oximes of Heterocyclic Ketones by Pyridinium Chlorochromate: A Kinetic and Mechanistic Study - Jani Bai, T.S.; Santhi, S. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of 2,6-diphenyl piperidin-4-one and its 3-alkyl substituted derivatives by pyridinium chlorochromate has been studied in aqueous acetic acid medium. The oxidation is first order each in [oxidant] and [substrate]. The reactions are acid catalyzed. The effect of ionic strength on the reaction rate is negligible. The reaction rate decreases with decrease in the dielectric strength of the medium indicating a polar mechanism. The reactions are followed at four different temperatures and the activation parameters computed. Based on the results obtained a plausible mechanism is proposed. The reactivity sequence is found to be PPO > 3- MePPO > 3-EtPPO > 3,3-diMePPO > 3-iprPPO.